Population pharmacokinetics of Amisulpride in Chinese patients with schizophrenia with external validation: the impact of renal function - Li, Anning; Mak, Wen Yao; Ruan, Tingyi; Dong, Fang; Zheng, Nan; Gu, Meng; Guo, Wei; Zhang, Jingye; Cheng, Haoxuan; Ruan, Canjun; Shi, Yufei; Zang, Yannan; et al. (Frontiers in Pharmacology, 2023)
Amisulpride is primarily eliminated via the kidneys. Given the clear influence of renal clearance on plasma concentration, we aimed to explicitly examine the impact of renal function on amisulpride pharmacokinetics (PK) via population PK modelling and Monte Carlo simulations. Plasma concentrations from 921 patients (776 in development and 145 in validation) were utilized. Amisulpride PK could be described by a one-compartment model with linear elimination where estimated glomerular filtration rate, eGFR, had a significant influence on clearance. All PK parameters (estimate, RSE%) were precisely estimated: apparent volume of distribution (645L, 18%), apparent clearance (60.5L/h, 2%), absorption rate constant (0.106 h -1 , 12%) and coefficient of renal function on clearance (0.817, 10%). No other significant covariate was found. The predictive performance of the model was externally validated. Covariate analysis showed an inverse relationship between eGFR and exposure, where subjects with eGFR=30 mL/min/1.73m 2 had more than 2-fold increase in AUC, trough and peak concentration. Simulation results further illustrated that, given a dose of 800mg, plasma concentrations of all patients with renal impairment would exceed 640ng/mL. Our work demonstrated the importance of renal function in amisulpride dose adjustment and provided a quantitative framework to guide individualized dosing for Chinese patients with schizophrenia.